The Return on IPO Stocks during the COVID-19 Pandemic in Indonesia - Wigantini, Ghea Revina; Nainggolan, Yunieta Anny (SBM ITB, 2022)
Abstract. Conducting an initial public offering (IPO) during the COVID-19 pandemic is not easy due to the current high level of economic uncertainty. This study aims to examine the effect of the COVID-19 pandemic on the initial return on IPO shares in Indonesia. In the study, a cross-sectional regression was applied, using a sample of 51 companies that conduct IPOs. It was found that the fear index over the COVID-19 pandemic negatively affected the initial return. The higher the fear index, the lower the return on IPO stocks on the first listing day. The results therefore demonstrates that the fear of COVID-19 influenced the IPO market return in Indonesia. This study extends the literature on the COVID-19 pandemic, especially on the initial return on IPOs. Practically, this research also provides insight into the issuers regarding the appropriate timing of IPOs during the crisis, particularly for investors who wish to buy IPO shares during an uncertain time. Policymakers are expected to mitigate the cases and deaths of COVID-19 in Indonesia, which may reduce investors’ fear related to COVID-19. This paper's limitation is that it only examines data from 2020, as this was the year in which COVID-19 first announced. Future research could include the short-term and long-term performance of IPOs, and also broaden the sample area to a larger region.Keywords: Initial return, IPO, COVID-19, fear index, Indonesia.Abstrak. Melakukan penawaran saham perdana (IPO) pada masa pandemi COVID-19 tidaklah mudah karena pada masa ini memiliki ketidakpastian ekonomi yang tinggi. Penelitian ini bertujuan untuk melihat pengaruh pandemi COVID-19 terhadap tingkat pengembalian awal saham yang melakukan IPO di Indonesia. Penelitian ini menggunakan regresi cross-sectional, dengan menggunakan sampel dari 51 perusahaan yang melakukan IPO. Penelitian ini menemukan bahwa indeks kepanikan atas pandemi COVID-19 mempengaruhi tingkat pengembalian awal secara negatif signifikan. Hasil penelitian menunjukkan bahwa indeks kepanikan atas pandemic COVID-19 menghantam pengembalian pasar IPO. Semakin tinggi tingkat indeks kepanikan atas pandemic COVID-19 maka semakin rendah tingkat pengedalian saham IPO pada hari pertama memasuki bursa. Penelitian ini mengembangkan literatur penelitian tentang pandemi COVID-19, terutama terhadap tingkat pengembalian awal IPO. Secara praktik, penelitian ini juga memberikan wawasan terhadap perusahaan atas waktu yang tepat untuk IPO bila terjadi krisis dan untuk investor yang ingin membeli saham IPO pada masa yang sedang tidak pasti. Para pembuat kebijakan diharapkan dapat memitigasi kasus dan kematian COVID-19 di tanah air untuk mengurangi kepanikan investor terkait COVID-19. Keterbatasan tulisan ini yaitu hanya mengkaji data tahun 2020 saat tahun pertama kali diumumkannya COVID-19. Ruang lingkup peneliti masa depan dapat mencakup kinerja IPO jangka pendek dan jangka panjang, dan juga memperluas sampel ke wilayah yang lebih besar.Kata kunci: pengembalian awal, IPO, COVID-19, indeks kepanikan, Indonesia.